Classifications on the travelling wave solutions to the (3+1)-dimensional generalized KP and Jimbo-Miwa equations - Isik, Ozlem; Degirmenci, Ozge Irmak; Bulut, Hasan (E D P Sciences, 2017)
In this paper, we use the powerful tan(F(xi)/2)-expansion method with the help of Wolfram Mathematica 9 to investigate the solution structures of two well-known nonlinear evolution equations, namely; the (3+1)-dimensional generalized KP and the (3+1)-dimensional Jimbo-Miwa equations. We obtain new solutions such as hyperbolic function, trigonometric function, exponential function and rational function solutions. We plot two-and three-dimensional graphics of some obtained results using the same program, Wolfram Mathematica 9.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY